Odpowiedź :
[tex]zad.a\\\\5^{7} \cdot 2^{7} =(5\cdot 2)^{7} =10^{7} \\\\zad.b\\\\6^{8} \div 3^{8}=(6\div 3 )^{8} =2^{8} \\\\zad.c\\\\0,4^{6} \cdot 15^{6} =(0,4\cdot 15 )^{6} =(\dfrac{4}{10} \cdot 15 )^{6}=(\dfrac{2}{5} \cdot \dfrac{15}{1} )^{6}=6^{6} \\\\zad.d\\\\(\dfrac{3}{5} )^{5} \div 3^{5} =(\dfrac{3}{5}\div 3)^{5} =(\dfrac{3}{5}\cdot \dfrac{1}{3} )^{5} =(\dfrac{1}{5} )^{5} \\\\zad.e\\\\(-2,7)^{8} \div (-\dfrac{9}{10}) ^{8} =(-\dfrac{27}{10} )^{8} \div (-\dfrac{9}{10}) ^{8}=[/tex]
[tex]=[(-\dfrac{27}{10} )\div (-\dfrac{9}{10} )] ^{8} ==[(-\dfrac{27}{10} )\cdot (-\dfrac{10}{9} )] ^{8} =3^{8}[/tex]
korzystam ze wzorów:
[tex]x^{n} \cdot y^{n} = (x\cdot y)^{n} \\\\x^{n} \div y^{n} = (x\div y)^{n}=(\dfrac{x}{y} )^{n} \\\\\dfrac{x}{y} \div \dfrac{a}{b} =\dfrac{x}{y} \cdot \dfrac{b}{a} =\dfrac{x\cdot b}{y\cdot a}[/tex]
Odpowiedź:
a)
[tex]5^{7} * 2^{7} =(5*2^){7} = 10^{7}[/tex]
b)
[tex]6^{8} : 3^{8} = 2^{8}[/tex]
c)
[tex]0,4^{6} * 15^{6} = ( 0,4*15)^{6} = 6^{6}[/tex]
d)
[tex](3/5)^{5} : 3^{5} = (\frac{3}{5} : 3 ) do piatej = ( 3/5*1/3)^{5} = ( 1/5)^{5}[/tex]
e)
[tex](-2,7)^{8} : ( - 9/10)^{8} = 2,7^{8} : ( 9/10)^{8} = ( 27/10*10/9^{8} = 3^{8}[/tex]
Szczegółowe wyjaśnienie: